Driving the ambulance: an essential component of emergency medical services: an integrative review - Julia Becker; Karin Hugelius (BMC Emergency Medicine, 2021)
Abstract Background The transport of patients from one location to another is a fundamental part of emergency medical services. However, little interest has been shown in the actual driving of the ambulance. Therefore, this review aimed to investigate how the driving of the ambulance affects the patient and the medical care provided in an emergency medical situation. Methods A systematic integrative review using both quantitative and qualitative designs based on 17 scientific papers published between 2011 and 2020 was conducted. Results Ambulance driving, both the actual speed, driving pattern, navigation, and communication between the driver and the patient, influenced both the patient’s medical condition and the possibility of providing adequate care during the transport. The driving itself had an impact on prehospital time spent on the road, safety, comfort, and medical issues. The driver’s health and ability to manage stress caused by traffic, time pressure, sirens, and disturbing moments also significantly influenced ambulance transport safety. Conclusions The driving of the ambulance had a potential effect on patient health, wellbeing, and safety. Therefore, driving should be considered an essential part of the medical care offered within emergency medical services, requiring specific skills and competence in both medicine, stress management, and risk approaches in addition to the technical skills of driving a vehicle. Further studies on the driving, environmental, and safety aspects of being transported in an ambulance are needed from a patient’s perspective.